Listening to complexity - Kozlova, Laetitia (Revista do Colóquio, 2025)
This essay is based on the sound installation I created for the exhibition MUṬIKKAPPAṬĀTA (Nov. 2024 – Jan. 2025) at the RAW Material Company – Center for art, knowledge, and society, as part of the Dakar Biennale. This exhibition is a journey into the intimate territories of Nathalie Vairac (b. 1972). The artist, based in Senegal, born in France to a Guadeloupean father and an Indian mother, traces her ancestry and confronts colonization. Back in her homeland, she writes and records. Vairac invited me to listen and stage her words in the curatorial space. With the help of sound practitioners Deshays and Chattopadhyay, and the pioneering work of composer Amacher, I explore expository strategies for the recorded spoken voice, and specifically the tension between the formal search for non-linearity, and the inherent linearity of listening, ensuring the preservation of meaning.